Postmigration Art, Culture, and Politics in Contemporary Europe - Post, Hans Christian; Schramm, Moritz; Gaonkar, Anna Meera (Postmigrantische Studien, 2021)
The concept of »postmigration« has recently gained importance in the context of European societies' obsession with migration and integration along with emerging new forms of exclusion and nationalisms. This book introduces ongoing debates on the developing concept of »postmigration« and how it can be applied to arts and culture. While the concept has mainly gained traction in the cultural scene in Berlin, Germany, the contributions expand the field of study by attending to cultural expressions in literature, theatre, film, and art across various European societies, such as the United Kingdom, France, Finland, Denmark, and Germany. By doing so, the contributions highlight this concept's potential and show how it can offer new perspectives on transformations caused by migration.